2010
DOI: 10.1084/jem.20091627
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD103+ dendritic cells form a unified subset developmentally related to CD8α+ conventional dendritic cells

Abstract: Although CD103-expressing dendritic cells (DCs) are widely present in nonlymphoid tissues, the transcription factors controlling their development and their relationship to other DC subsets remain unclear. Mice lacking the transcription factor Batf3 have a defect in the development of CD8α+ conventional DCs (cDCs) within lymphoid tissues. We demonstrate that Batf3−/− mice also lack CD103+CD11b− DCs in the lung, intestine, mesenteric lymph nodes (MLNs), dermis, and skin-draining lymph nodes. Notably, Batf3−/− m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
726
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 641 publications
(781 citation statements)
references
References 60 publications
(127 reference statements)
46
726
1
8
Order By: Relevance
“…These findings support the hypothesis that mammalian cross-presenting DCs, including murine lymphoid CD8 + DCs, murine tissue CD103 + DCs, and the human CD141 lineage, share a common ancestor that has been conserved through evolution in teleost fish. Previous evidence that led other investigators to formulate the hypothesis includes the expression of common transcription factors, such as Batf3 (20,21) and IRF8 (18,19), the sensitivity to TLR3 ligands, and the use of CLEC9A and XCR1 (18,19,(22)(23)(24)29). We were able to identify CLEC9A and XCR1 homologs in trout EST databases, but we showed that the skin CD8 + DC-like subpopulation expressed both Batf3 and IRF8, distinctive transcription factors essential in the development of cross-presenting DCs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These findings support the hypothesis that mammalian cross-presenting DCs, including murine lymphoid CD8 + DCs, murine tissue CD103 + DCs, and the human CD141 lineage, share a common ancestor that has been conserved through evolution in teleost fish. Previous evidence that led other investigators to formulate the hypothesis includes the expression of common transcription factors, such as Batf3 (20,21) and IRF8 (18,19), the sensitivity to TLR3 ligands, and the use of CLEC9A and XCR1 (18,19,(22)(23)(24)29). We were able to identify CLEC9A and XCR1 homologs in trout EST databases, but we showed that the skin CD8 + DC-like subpopulation expressed both Batf3 and IRF8, distinctive transcription factors essential in the development of cross-presenting DCs.…”
Section: Discussionmentioning
confidence: 81%
“…Recent data suggest that, in mice, both of these cross-presenting DCs, lymphoid CD8a + DCs and tissue-derived CD103 + DCs, form a common DC lineage. The functionality of these two DC subtypes is dependent on similar transcription factors (17), and they are derived exclusively from pre-DCs under the control of Flt3 ligand, IFN regulatory protein (IRF)8 (18,19), and Batf3 (20,21). Additionally, both populations use the CLEC9A lectin to recognize necrotic cells (22) and express the chemokine receptor XCR1 (23).…”
Section: Endritic Cells (Dcs) Belong To the Family Of Professionalmentioning
confidence: 99%
“…38 Series of our studies have shown that pDCablated mice exhibited a near-complete and specific elimination of pDCs in the lymphoid tissues following DT treatment, but they retained other leukocytes, including cDC subsets. 31,32 Analysis of pDC-ablated mice revealed that the development of DSS-induced acute colitis was attenuated in the absence of pDCs.…”
Section: Discussionmentioning
confidence: 90%
“…Mice deficient in Batf3 have normal numbers of precursors, including CDPs and pre-cDCs [85], and appear deficient in only the most terminal stage of CD8 + DC maturation. This final step is defined by the induction of genes important for the function of this DC subset, including Langerin and CD103.…”
Section: Factors Regulating Late DC Progenitor Developmentmentioning
confidence: 99%